A deep view-point language and framework for projective modeling. Issue 101 (November 2021) - Atkinson, Colin; Tunjic, Christian
Abstract: Most view-based modeling approaches are today based on a "synthetic" approach in which the views hold all the information modeled about a system and are kept consistent using explicit, inter-view correspondence rules. The alternative "projective" approach, in which the contents of views are "projected" from a single underlying model on demand, is far less widely used due to the lack of suitable conceptual frameworks and languages. In this paper we take a step towards addressing this problem by presenting the foundations of a suitable language and conceptual framework for defining and applying views for projective modeling. The framework leverages deep modeling in order to seamlessly support views that exist at, and span, multiple levels of classification. The viewpoint language was developed in the context of Orthographic Software Modeling but is more generally applicable to any projective modeling approach.